Individualized cardiovascular risk assessment by cardiovascular magnetic resonance. (March 2014) - Hinojar, Rocio; Botnar, Rene; Kaski, Juan Carlos; Prasad, Sanjay; Nagel, Eike; Puntmann, Valentina O
ABSTRACT: : Cardiovascular magnetic resonance (CMR) is gaining clinical importance in preventive medicine. Evidence on diagnostic accuracy and prognostic value, in addition to the development of faster imaging, increased availability of equipment and imaging expertise have led to a wide-spread use of CMR in a growing number of clinical indications. The first part of this review summarizes the role of CMR biomarkers for risk assessment focusing on the patients groups that benefit from the use of CMR. In the second part, the future directions for CMR are discussed and their role in prevention of cardiovascular disease.